1983
DOI: 10.1038/303815a0
|View full text |Cite
|
Sign up to set email alerts
|

HLA-D region β-chain DNA endonuclease fragments differ between HLA-DR identical healthy and insulin-dependent diabetic individuals

Abstract: The human HLA-D histocompatibility region encodes class II antigens each of which consists of two polypeptide chains (alpha and beta) inserted in the plasma membrane. These molecules are implicated in the regulation of the immune response but several human diseases are also found to be associated with certain HLA-DR antigens. The occurrence of insulin-dependent (type I) diabetes (IDDM) is strongly associated with HLA-DR3 and/or 4 (ref. 5). The class II antigens, however, show a marked genetic polymorphism asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
91
3

Year Published

1985
1985
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 258 publications
(104 citation statements)
references
References 16 publications
10
91
3
Order By: Relevance
“…It has long been known that the first intervening sequence in DQB from diabetic patients is different from that of normal HLA-DR matched control subjects [3,4,51]. Also, a wealth of regulatory sequences has been uncovered in the DQB and DQA genes [52,53], with no inkling as to their possible significance in the pathogenesis of this disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has long been known that the first intervening sequence in DQB from diabetic patients is different from that of normal HLA-DR matched control subjects [3,4,51]. Also, a wealth of regulatory sequences has been uncovered in the DQB and DQA genes [52,53], with no inkling as to their possible significance in the pathogenesis of this disease.…”
Section: Discussionmentioning
confidence: 99%
“…In insulin-dependent diabetes mellitus (IDDM), genetic linkage in Caucasian populations has been shown for the serologically-defined antigens DR3 and DR4, while DR2 has been shown to confer protection from the disease [2]. Later studies revealed that this was due to linkage disequilibrium of these alleles to various DQ alleles [3,4]. Furthermore, genes telomeric and centromeric to HLA-DQ were shown to be less highly associated with the disease than DQ itself [5], Of even greater significance is the fact that susceptibility to diabetes can be conferred by DQ A and B genes in trans position giving credence to the hypothesis that DQ molecules are true susceptibility genes for IDDM [6].…”
mentioning
confidence: 99%
“…The DQw8 serological specificity, previously called DQw3.2, is associated with type I (insulin-dependent) diabetes, whereas the DQw7 specificity, previously called DQw3.1, is not associated with type I diabetes (3)(4)(5)(6)(7)(8)(9). Tait et al (10) recently reported that the DQw8 association exists only in type I diabetic individuals who type as HLA-DR4/3.…”
mentioning
confidence: 99%
“…class II HLA-DQA1, -DQB1, and -DRB1 loci determine whether a haplotype is associated with susceptibility, or protection, to type 1 diabetes (Owerbach et al 1983 ;Svejgaard et al 1989 ;Todd et al 1989 ;Cucca & Todd, 1996 ;She, 1996). Direct sequence analysis has demonstrated that the effect of the different DQ molecules can, in part, be correlated with amino acid variation at residue 57 of the DQβ chain (Todd et al 1987).…”
mentioning
confidence: 99%